BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT. INDOSAT M2 - Silvi Andika Citra; Anthon Rustono (Jurnal Riset Bisnis dan Manajemen, 2018)
High levels of delay and turnover rates indicate a problem with employee job satisfaction. Several factors that can affect employee job satisfaction are organizational culture and motivation. This study aims to determine the organizational culture, motivation and job satisfaction of employees at PT. Indosat M2 Provisioning & Maintenance Department. The research method used is quantitative method. The type of analysis used is descriptive and using multiple linear regression. Sampling technique in this study using nonprobability sampling by using sample saturated a number of 46 respondents. Data collection was done through questionnaires. Based on the results of data processing, it is known that the employee’s assessment of organizational culture is 75.37%, motivation is 75.58% and job satisfaction is 70.65%, it means that organizational culture, motivation and job satisfaction are in high category. The overall results support that organizational culture and motivation have a positive and significant effect on employee work satisfaction of PT. Indosat M2 Provisioning & Maintenance Department.